The Role of Ethical Leadership in Reducing the Phenomenon of Job Hypocrisy: Case Study -The Technical and Vocational Training Corporation in Jazan - Taj eldeen Ibrahim Shaa eldeen, Fath elrahman (Technium Education and Humanities, 2025)
This study aimed to identify the role of ethical leadership in reducing the phenomenon of job hypocrisy. The researcher employed a descriptive analytical approach to examine the study's variables. A questionnaire consisting of (40) items was utilized as the data collection tool and was distributed to employees of the Technical and Vocational Training Corporation in Jazan. A random sample of (176) individuals was selected for the study. The findings revealed that the sample members demonstrated a high perception of ethical leadership, with a mean score of (3.872), while also exhibiting a high level of job hypocrisy, with an average score of (3.934). Additionally, the study identified a statistically significant role for ethical leadership—across its dimensions, including personal qualities, administrative qualities, human relations, and teamwork in reducing job hypocrisy. The study concluded with several recommendations, the most significant of which include: promoting a culture of integrity and ethics at all organizational levels, developing training courses and workshops to educate employees about the importance of integrity, enhancing mechanisms for reporting ethical violations to ensure confidentiality and protect whistleblowers, and establishing strict internal policies to address instances of job hypocrisy while fostering ethical values.